The perception of parental attitudes and styles to deal with stress among the young attending to athletic championship schools - Mateusz Minda (Kazimierz Wielki University, 2019)
Introduction and purpose of the work: Parental attitudes perceived by adolescents, and not only parental upbringing impacts, can significantly help young people playing sports developing their careers. In turn, sport itself can strengthen their self-esteem, and also shape their ability to cope with stress. Being an athlete-student exposes young people to experiencing various types of stressors related to training and competitions on the one hand, and the fulfillment of compulsory education on the other. The aim of the study was to check the links between the perception of parental attitudes and students' styles of coping with stress attending the Athletic Championship Schools. Materials and method: The study involved 51 students aged 16 to 20, including 28 girls (55%) and 23 boys (45%) attending the Athletic Championship School (upper secondary stage). The mean age was 17.8 and the standard deviation was 1.12. To measure the perception of parental attitudes, the Parental Attitude Scale - 2 (SPR-2) by Plopy (2012) was used, which is a shortened version of the Parental Attitude Scale (SPR) for young people. In turn, stress management styles were measured using the Coping Inventory for Stressful Situations (CISS) by Endler and Parker in the polish adaptation of Szczepaniak, Strelau and Wrześniewski. Results: Obtained results revealed that there is a correlation between perceived negative mother attitudes (excessive demands, inconsistency) and emotion-focused style. Significant links between perceived negative father attitudes (excessive demands, inconsistency) and avoidance-focused style, were also found. It was proved that the intensity of positive attitudes of both father and mother was higher than negative attitudes among the surveyed youth attending AChS. Conclusions: It is significant to remember, when working with young people playing sports, about family contact, which is associated with coping styles, and that effectively managing stress is a key skill that every player should have. The obtained research results are an important contribution to expanding knowledge about the relationship between parental attitudes and styles of coping with stress, especially among young athletes, although they do not allow to formulate the final conclusions.